Assessment of Pattern and Sustainability of Livestock Diversification in Odisha - Pattanayak, Urmi; Naik, Kalu (Annals of Arid Zone, 2022)
The present paper described the pattern and sustainability of livestock diversification in 30 districts of Odisha. Secondary data of livestock census were used in computing Simpson diversification index and composite index. The study reveals that during the censual period 1992 to 2012, the individual pattern of crossbred cattle and goat has been declined in the state. Similarly, the pattern of fowls was also decreased by -58.20% for the same period. However, duck and other birds have shown increase. The Khordha, Nuapada, Rayagada, Subarnapur are the least diversified districts during the censual period 2007. While the analysis on inter-composite index comparison showed that all the 30 districts have less agricultural index but with more infrastructural and social indicators put together implying that the study region is more livestock and poultry pattern. The few suggestions towards more diversification in the state is to increase marketing outreach, enhancement of income of farmers through artificial insemination for genetic improvement of indigenous cattle and buffalo, to increase the animals health care centres to achieves the long term goals and diversify the livestock sectors in the state.